Clinical performance of rheumatoid arthritis impact of disease score: A real-life evidence from the multicenter nationwide registry BioStaR - Alkan Melikoğlu, Meltem; Ataman, Şebnem; Bodur, Hatice; Çay, Hasan Fatih; Çapkın, Erhan; Akgül, Özgür; Çevik, Remzi; Göğüş, Feride; Kamanlı, Ayhan; Yurdakul, Fatma Gül; Gürer, Gülcan; Yağcı, İlker; et al. (Springer Heidelberg, 2021)
The rheumatoid arthritis impact of disease (RAID) score was developed as a patient-derived composite response index for the evaluation of the disease impact on cases with rheumatoid arthritis (RA). The aim of this study was to evaluate the psychometric properties and performance of RAID score in the real-life settings. Cases with RA from our multi-center, nationwide registry called Biologic and targeted Synthetic antirheumatic drugs Registry RA (BioStaR RA) were included in this cross-sectional observational study. Demographic data, disease duration, pain, patient's global assessment (PGA) and physician's global assessment (PhyGA) were recorded. DAS28-ESR, DAS28-CRP, the simplified disease activity index (SDAI) and the clinical disease activity index (CDAI) were assessed as disease activity evaluations. The health assessment questionnaire-disability index (HAQ-DI) and RAID were completed by all the participants. The construct validity was tested by the analysis of correlations between RAID score and scores of PGA, disease activity indexes and HAQ-DI. We also evaluated the discriminatory ability of RAID to distinguish patients with different levels of disease activity and disability and the cut-off values were calculated by ROC analysis. 585 cases with RA were included in this investigation. The RAID score was significantly positively correlated with PGA, all disease activity indexes and HAQ-DI (p < 0.001). The discriminatory ability of RAID score in different disease activity and disability groups was also demonstrated (p < 0.001). To estimate DAS28-ESR (remission/low + moderate + high), RAID score cut-off points were 2.88 (sensitivity 73%, specificity 62%), 3.23 (sensitivity 75%, specificity 60%) and 3.79 (sensitivity 74%, specificity 58%), respectively. Our study indicated that RAID was a reliable tool in daily clinical practice by presenting its correlations with disease activity and disability assessments and by showing its discriminatory ability in these parameters in the real-life experiences.
Keywords: Rheumatoid Arthritis; The Rheumatoid Arthritis Impact of Disease (RAID); Construct Validity; Discriminatory Ability